An efficient scheme for battery assisted solar energized uninterrupted water supply utilizing switched reluctance motor drive. (24th November 2021) - Mishra, Anjanee Kumar; Singh, Bhim
Abstract: This work deals with a high gain (HG) DC‐DC converter integrated scheme for solar power‐fed water pump with battery energy storage (BES). The developed scheme confirms a reliable solution for non‐interruptible water streaming under all environmental situations. The battery integrated with the system performs the functionality of a secondary energy source. The controller developed for the bidirectional converter at the battery side is incorporated the solar parameters. Hence, it enhances the dynamic performance of the charging‐discharging of BES under varying environmental situations. The performance of solar panel output is optimized using an HG positive output Luo (POL) converter using the maximum power point tracking (MPPT) algorithm. The simulation is carried out to confirm the effectiveness of the present scheme. The captured performances are authenticated through experimental results on a present system. Abstract : Schematic of developed grid integrative water pumping system.